Mental Toughness Profiles and Their Association with Grief Levels in Orphanage Adolescents - Eris Irawan; Agung Nugraha; Gian Sugiana Sugara (POTENSI : Journal of Education and Human Development, 2025)
Grief is an emotional experience that arises from significant loss and can affect the psychological well-being of adolescents, particularly those living in orphanages. In this context, mental toughness serves as a protective factor that plays an important role in helping adolescents manage emotional stress and adapt to challenging situations. This study aims to analyze the correlation between grief levels measured using the Prolonged Grief Disorder Revised (PGD-R13) and mental toughness measured using the Mental Toughness Scale (SKM-24) among orphanage adolescents. The study employed a quantitative approach with a correlational design. The findings indicate that a portion of the adolescents fell into the normal grief category, while others showed symptoms of syndromal grief and prolonged grief. Regarding mental toughness, most adolescents were in the moderate category, although a significant proportion scored low on the control and confidence dimensions. Correlation analysis revealed a negative relationship between grief levels and mental toughness, indicating that the higher the grief symptoms experienced by the adolescents, the lower their level of mental toughness. These findings suggest that experiences of loss and instability in caregiving environments influence adolescents’ ability to manage psychological distress and maintain adaptive functioning. This study highlights the importance of interventions focused on strengthening emotion regulation, enhancing self-confidence, and providing psychological support to help orphanage adolescents cope with grief while improving their mental toughness.